Mechanisms of Resistance to Quinolones and Epidemiological Significance of Salmonella spp. - Velhner Maja (Acta Veterinaria, 2016)
Bacteria develop resistance to antimicrobial agents by a number of different mechanisms. The resistance to (fluoro)quinolones in Salmonella is of particular importance especially if therapy in humans is required. For decades there has been a significant interest in studying the biology of Salmonella because these bacteria are among the leading causes of foodborne illnesses around the globe. To this date, two main mechanisms of quinolone resistance have been established: alteration in the targets for quinolones, decreased accumulation inside bacteria due to impermeability of the membrane and/or an over expression of the efflux pump systems. Both of these mechanisms are chromosomally mediated. Furthermore, mobile elements have been described carrying the qnr gene which confers resistance to quinolones. The plasmid encoded QNR proteins belong to the pentapeptide repeat family of proteins. The plasmid mediated quinolone resistance (PMQR) is often associated with the resistance to beta lactam antibiotics. It was noticed that PMQR is backing up chromosomal mutations for quinolone resistance, hence becoming an important resistance mechanism worldwide. Even with our knowledge expanding over the years, it is not possible to predict how bacteria will respond in the future, if they are exposed to new external challenges. The possibility that they will find a way to survive by introducing new mutations or by exchanging mobile genetic elements and subsequently developing resistance to survive in the environment should not be underestimated.